Bulian Saa: Exploring the Distinct Characteristics of Ritual Language of North Bali’s Indigenous Community - Sumaryana Putra, I Komang; Saad , George; Nugraheni Saraswaty, Amrita; Surya Jayadi , I Kadek (Universitas Udayana, 2025)
Bulian Saa is a distinct form of Balinese Hindu ritual language used by the Bali Mula, the indigenous Balinese community of Bulian Village, North Bali. Unlike other Balinese Hindu ritual languages, Bulian Saa exhibits lexical and structural features that diverge significantly from the standardized ritual language used across Bali, particularly in the names of deities, temples, and sacred elements. This research explores Bulian Saa in comparison with standard Balinese Hindu ritual language, with a focus on the Panca Sembah (Five Turns of Worship). This comparison enables a thorough investigation of the unique characteristics of Bulian Saa that are reflected in language identity and language preference of Balinese Hindu people in Bulian village. The study’s significance lies in documenting and analysing this under-researched variant of Balinese ritual language, fostering its preservation, and providing insights for broader discussions on the relationship between language, tradition, and identity in minority communities.